(untitled) (Bangladesh Journal of Botany, 2022)
More than 70 % soils of Odisha are acidic with dominance of Fe and Al where Mo deficiency in soils affects the yield of rabi green gram which is much below than the national average. With this background an experiment was conducted by soil application four dose of molybdenum (0, 250, 500, 750 g/ha) and two foliar spraying of molybdenum @0.1% Mo (F1) and 0.2% Mo (F2) on the variety IPM 02-14. A light texture acidic sandy loam soil of central farm, OUAT, Bhubaneswar which is dominated by micronutrients like Fe, Mn, Al and deficient in molybdenum was selected for the experiment. It was observed that growth and yield attributing characters increased with the increase in foliar spraying (FS) of molybdenum as well as combined application of foliar and soil application up to a dose of (250 g/ha soil application with 0.2% foliar application of Mo) after which a decrease in all the attributes was observed. The highest yield of green gram was 549 kg/ha at combined application of 250 g/ha soil with 0.2% foliar spray of molybdenum. Uptake of major nutrients (N,P and K)was increased and the highest uptake was at Mo3F2. Improvement in soil fertility was observed in post-harvest soil with a positive balance in availability of nitrogen after meeting the crop requirement. Therefore, application of both soil and foliar spray (250 g/ha soil with 0.2%) was optimum dose of Mo for green gram grown in low fertile and Fe rich acidic soil. Bangladesh J. Bot. 51(4): 689-696, 2022 (December)